INOVASI SISTEM PELAYANAN PEMBAYARAN PAJAK BUMI DAN BANGUNAN PERDESAAN PERKOTAAN (PBB-P2) BERBASIS ONLINE MELALUI QUICK RESPONSE INDONESIAN STANDARD (QRIS) DI BAPENDA TIMOR TENGAH SELATAN - Banu, Yohan Siprianus; Therik , Jeni Jacoba; Rene , Mariayani O; Toda , Hendrik (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
Innovation is an idea, practice, or object that is considered new by an individual or group of individuals. Someone considers something a new idea because what is seen/heard is something that is justified without the opinions of others or personal views. Innovation in public services is currently a must in order to improve and improve the effectiveness of public services. In this case, the PBB-P2 Online payment service system through QRIS is an innovation carried out by the regional government of Timor Tengah Selatan (TTS) Regency. This study aims to determine the innovation of the PBB-P2 payment service system based on Online through QRIS at the Regional Revenue Agency of Timor Tengah Selatan Regency. The researcher conducted data analysis using the results of the study of Evert M. Rogers' (1995) Defusion of Innovation theory. That there are five stages in the innovation decision process, namely the knowledge, persuasion, decision, implementation and confirmation stages. The type of research used is descriptive research with a qualitative approach. The results of the study show that there are still many PBB-P2 taxpayers who do not know and do not use the PBB-P2 payment innovation through QRIS. Judging from the implementation of innovation to the innovation decision process, it has not been successful in TTS Regency. This can be seen from several problems found, namely the absence of regulations in the application of QRIS innovation in PBB-P2 payments, the absence of a budget for the implementation of QRIS innovation so that there is no socialization of how to use QRIS in PBB-P2 payments, TTS taxpayers still experience obstacles in using digital wallets such as inadequate RAM on Android phones, many people are not yet proficient in using Android phones to access the PBB-P2 payment system via QRIS, therefore cooperation is needed between various stakeholders in the implementation of the PBB-P2 payment service system via QRIS as a public service media.